(untitled) (Indian Journal of Arid Horticulture, 2025)
Tomato (Lycopersicon esculentum Mill.) is one of the popular and important commerc ial vegetable crop of India. It is available through out the year and in Rajasthan’s vegetable scenario, it ranks second in production (54,490 MT) after onion (Anonymous, 2005). The main tomato growing districts ofRajasthan are Jaipur, Al war, Tonk, Sirohi, Pali and Udaipur. Tomato is a good source ofVitamin A, B, and C, possess medicinal properties and is said to be an excellent purifier of blood (Aykrod, 1963 ).